Conversion in the Fourth Gospel - Ledwoń, Dawid (2022)
The essence of the proclamation of the Good News is a call to conversion, which seems absent from the Fourth Gospel due to the lack of any direct reference. The biblical idea of conversion is first expressed there by a call to believe in Jesus as the Son of God; then by the repeated motif of coming out of darkness into the light, approaching and discovering (accepting) the truth; being born of God and the Spirit, approaching Jesus, testifying about him, accepting and following him, and finally glorifying God. This study aims to present this multi-faceted process, whose framework is outlined by John, first in the prologue to his Gospel and then developed in the narrative. The same order is applied in the individual stages of this analysis employing a synchronic approach, which enables the readers to derive the edifying call to turn to Jesus and follow him to gain eternal life from the final, i.e., canonical, version of John’s text.